Evaluating the antioxidant effects of human hair protein extracts - Lai, Hui Ying (2022)
The intrinsically high cysteine content in human hair keratins and keratin associated proteins confer hair its outstanding mechanical strength through the formation of strong intermolecular disulfide bonds. In addition, these proteins offer the potential to be exploited as potent antioxidants. This report presents our findings on the antioxidant effects of human hair protein extracts and their consequent protective role against oxidative stress in human dermal fibroblast (HDF) cultures. Protein extracts were obtained from human hair using sodium sulfide as the reducing agent, and characterized using SDS-PAGE, Western blotting, MALDI-ToF mass spectrometry and amino acid analysis. Cysteine was found to account for 11.2 mol % in the extracted fractions. By measuring 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) radical scavenging activity, the hair protein fractions were shown to possess significant antioxidant ability (IC50 = 16.22 μM). As a supplement in cell culture media, the extracts protected HDFs from H2O2 induced oxidative stress, which was demonstrated by the maintenance of cell viability and reduced reactive oxygen species production. Besides offering mechanical support as a scaffolding material, the unique antioxidizing ability of human hair protein extracts may also be exploited in biomedical applications.